Project managers guide to Microsoft Project 2019 : covers standard, professional, server, web application, and Office 365 versions - Cicala, Gus (Apress, 2020)
This guide is an all-in-one training resource and reference that covers all versions found in the Microsoft Project 2019 suite. It is not a "how-to" manual covering the features and functions of the software, but is designed to explain and demonstrate why those features and functions are important to you as a project manager, allowing you to maximize the value of Microsoft Project 2019. Each aspect of project-manager-specific coverage was selectively compiled by author and Microsoft Project expert Cicala over more than two decades of consulting, project management training, and managing real-world projects using Microsoft Project. Readers will appreciate the robust index and intuitively organized and learning-oriented chapters, and sub-sections for quick reference and problem solving. "Try it" exercises at the close of every chapter help ensure understanding of the content.